The successful development and implementation of an off campus triage system during the COVID-19 pandemic in Guangdong, China - Xie, Ri-hua; Chen, Yanfang; Xiong, Ziyu; Wang, Jie; Zhou, Lepeng; Li, Ning; Pakhale, Smita; Cameron, D William; Krewski, Daniel; Wen, Shi Wu (International Journal of Infection Control, 2021)
To deal with the public health crisis caused by the coronavirus disease 2019 (COVID-19) outbreak, we developed an off campus triage system at entry points to the outpatient, emergency, and inpatient departments. To enhance this off campus triage system, we implemented intensive staff training and made detailed triage plans with a timely referral. Of the 85,414 patients/visitors who visited The Seventh Affiliated Hospital of Southern Medical University, one of the government-designated hospitals to triage-suspected COVID-19 patients between January 22 and March 10, 2020, 359 patients were triaged to the COVID-19 fever clinic and 1,218 were triaged to the general fever clinic; 187 were suspected of COVID-19 infection and quarantined; and four cases of COVID-19 were confirmed and referred. During the outbreak, no inhospital infection and no complaint from patients and their family members occurred, and up to September 10, 2020, no new cases of COVID-19 in this hospital or its catchment area were detected. The off campus triage system is an effective approach to improve the detection of COVID-19 infection and reduce inhospital cross infection.